Lactic Acid Bacteria With Antioxidant Activities Alleviating Oxidized Oil Induced Hepatic Injury in Mice - Lin, Xiangna; Xia, Yongjun; Wang, Guangqiang; Yang, Yijin; Xiong, Zhiqiang; Lv, Fang; Zhou, Wei; Ai, Lianzhong (Frontiers in Microbiology, 2018)
In order to screening new antioxidative Lactic acid bacteria (LAB) strains to alleviating liver injury induced by oxidized oil, we isolated and screened LAB from Chinese fermented foods. Lactobacillus plantarum AR113, Pediococcus pentosaceus AR243, and Lactobacillus plantarum AR501 showed higher scavenging activity of α, α-Diphenyl-β-Picrylhydrazyl (DPPH) free radical and hydrogen radical, stronger inhibition of lipid peroxidation, and better protective effect on yeast cells in vitro. In vivo, oral administration of L. plantarum AR501 improved the antioxidant status of injury mice induced by oxidized oil including decreasing lipid peroxidation, recovering activities of antioxidant enzymes. Meanwhile, the gene expression of Nuclear factor erythroid 2-related factor 2 (Nrf2) of L. plantarum AR501 group was markedly elevated, and several antioxidant genes such as glutathione S-transferase (GSTO1), heme oxygenase-1 (HO-1), Glutamate cysteine ligase (GCL) and NAD(P)H:quinone oxidoreductase-l (NQO1) were subsequently up regulated in mice liver. Therefore, L. plantarum AR501 could be considered as potential candidates for production of functional foods that can alleviate the oxidative damage induced by oxidized oil.